Concept Design and Development of an Electric Go-Kart Chassis for Undergraduate Education in Vehicle Dynamics and Stress Applications - Tihomir Mihalić; Josip Hoster; Vladimir Tudić; Toni Kralj (Applied Sciences, 2023)
This paper presents an approach to a go-kart chassis design, vehicle dynamics calculation, Li-ion battery capacity analysis, and electric motor choice for optimized vehicle performance. The chassis analysis shown in this paper was performed using a CAD/FEA software package, SolidWorks Student Edition. Three highlights can be found in this paper: (1) An original design was implemented; the basic analysis was composed of chassis optimization using beam elements and modeling such an optimized chassis “locally” with solid elements for sub-modeling purposes. (2) The most stressed tube joint was sub-modeled to calculate the risk of tube wall stability. (3) Vehicle dynamics were calculated for the case of braking on a curved path and the case of a collision with the front tire due to road imperfection. The authors intend to install a data acquisition system in the future to analyze the stress of local chassis tubes. The results of the SolidWorks analysis indicate a safety design for the chassis concept. The results for the sub-model stability (buckling) analysis show that the chosen tube wall thickness-to-diameter ratio gives safety factor values ranging from 1.6 to 5. Based on the stress distribution, some improvement in the middle part of the chassis can be made by using a half-a-millimeter-thicker wall tube or a larger tube diameter of a few millimeters to lower the stress. The latter will be described in this paper.